Sustainable and traditional technologies in Kutahya historic houses and their contribution to circularity: the case of Lajos Kossuth house - Betül Ankaralıgil; Gülşen Dişli (Vitruvio: International Journal of Architectural Technology and Sustainability)
It is important to preserve historic buildings in their original conditions, not only to protect building integrity but also to sustain Traditional Knowledge Systems. As stated by ICCROM, those Traditional Knowledge Systems play an important role in the conservation and management of heritage. Among them, building service systems including heating, cooling, ventilation, lighting, drainage, and their architectural construction technology help sustain heritage buildings and extend their life cycle with a minimum level of energy demand. Passive survivability means also contribute to comfort conditions, opening new scenarios for the designing of contemporary buildings. Hence, in this research, first, traditional Kutahya houses were examined in terms of their construction, technology, and architecture. Then, among them, Lajos Kossuth House, dated the 18th century, has been chosen as an exemplary to investigate its traditional building service systems in more detail from the point of circularity in construction, their contribution to circular economy, Cradle to Cradle (C2C) strategies, and design for adaptability principles (DfA).  It is observed that they are mostly in a well-preserved condition in terms of both function and character-defining features. However, after 1982, during its refurbishment work to be used as a museum, some of its original details, especially the ones related to waste and clean water were destroyed. To be able to sustain and protect the rest of the original service systems and related architectural construction details in this case study building, they should first be documented, well defined and their recognition should be increased to serve as a model for the maintenance of similar building systems. In addition, it might be possible to transfer the knowledge of those passive survivability means and circular construction principles to contemporary buildings.